Negative Affectivity, Authoritarianism, and Anxiety of Infection Explain Early Maladjusted Behavior During the COVID-19 Outbreak - Bochicchio, Vincenzo; Winsler, Adam; Pagliaro, Stefano; Pacilli, Maria Giuseppina; Dolce, Pasquale; Scandurra, Cristiano (Frontiers in Psychology, 2021)
During the first phase of the COVID-19 outbreak, Italy experienced problems of public order and maladjusted behavior. This study assessed the role of negative affectivity, right-wing authoritarianism, and anxiety of COVID-19 infection in explaining a variety of the maladjusted behaviors (i.e., “China-phobic” discrimination, panic buying) observed with an Italian sample. Specifically, we examined the effect of Negative Affectivity and Right-Wing Authoritarianism on maladjusted behaviors, and the moderating role of anxiety of infection. Seven hundred and fifty-seven Italian participants completed an online survey between March 3rd to the 7th 2020, which was immediately before the lockdown. A moderated-mediation model was tested using a structural equation modeling approach. Results indicated that both Negative Affectivity and Right-Wing Authoritarianism were positively associated with COVID-19-related maladjusted behavior, and that Right-Wing Authoritarianism mediated the relationship between Negative Affectivity and maladjusted behavior. Furthermore, the effect of Right-Wing Authoritarianism on maladjusted behavior was greater for those with high anxiety of infection, and the indirect effect of Negative Affectivity on maladjusted behavior through Right-Wing Authoritarianism was moderated by infection anxiety. Findings highlight potential psychological paths that may inform communication strategies and public health initiatives aimed at promoting healthy behavior during an outbreak.